Pengaruh Pelatihan dan Pengembangan, Keterikatan Karyawan terhadap Kinerja Karyawan dengan Learning Culture sebagai Variabel Moderasi: (Survei pada Karyawan Yogya Group PT. Akur Pratama Regional Priangan Timur) - Subhan Riyanto; Kartawan Kartawan; Edy Suroso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aimed to analyze the influence of training and development, employee engagement, learning culture on employee performance at Yogya Group PT. Akur Pratama Regional Priangan Timur, as well as the role of learning culture in moderating the relationship between training, development, and employee engagement on employee performance. This research used a survey method with a quantitative approach, involving 175 staff and supervisors. Data analysis was conducted using Partial Least Square-Structural Equation Model (PLS-SEM), which proved that training and development, employee engagement, and learning culture had a positive and significant influence on employee performance. Learning culture also strengthened the relationship between training, development, and employee engagement on employee performance.